Characterization of dioxin-like activity of sediments from a Czech river basin - Hilscherova, K; Kannan, K; Kang, Y S; Holoubek, I; Machala, M; Masunaga, S; Nakanishi, J; Giesy, J P (Environmental toxicology and chemistry, 2001)
Synthetic organic chemicals are present in environmental compartments as complex mixtures and therefore their potential effects are difficult to predict. In this study, in vitro bioassays using wild-type fish and rat hepatoma cell lines and their corresponding recombinant cell systems were used to evaluate 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD)-like activity in extracts of sediments collected from rivers of the Czech Republic. All the sediment extracts elicited statistically significant responses in all the cell lines tested. For most sediment extracts, a complete dose-response relationship was obtained. The maximal efficacy of the samples was between 57 and 143% of the maximal induction elicited by TCDD. Greater responsiveness, sensitivity, and reproducibility were observed for recombinant than wild-type cells. Cell line-specific differences in the sensitivity to compounds present in the complex sediment extracts were observed. The TCDD equivalents (TCDD-EQs) determined from the different cell bioassays were correlated. Greater concentrations of TCDD-EQs were obtained with fish cell lines. The TCDD-EQs calculated from the results of chemical analysis of toxic equivalents (TEQs) were in good agreement with those determined by bioassays; the arly hydrocaron receptor (AhR)-effects of the identified chemicals appear to be generally additive. This indicates that most of the TCDD-like activity was accounted for by the compounds identified and quantified by instrumental analysis. Fractionation along with mass-balance calculations allowed identification of the active fractions and classes of compounds. Polycyclic aromatic hydrocarbons (PAHs) were found to be responsible for most of the AhR-mediated activity in sediments.
Keywords: nádorové buňky kultivované; geologické sedimenty; Dose-Response Relationship, Drug; hepatocelulární karcinom; polychlorované dibenzodioxiny; Reproducibility of Results; vztah mezi dávkou a účinkem léčiva; polycyklické aromatické uhlovodíky; Biological Assay; reprodukovatelnost výsledků; Rats; Carcinoma, Hepatocellular; Tumor Cells, Cultured; Environmental Pollutants; ryby; Animals; Water Pollutants, Chemical; zvířata; Fishes; biotest; Polychlorinated Dibenzodioxins; Geologic Sediments; Liver Neoplasms; krysa rodu Rattus; nádory jater; Environmental Monitoring; Polycyclic Aromatic Hydrocarbons; monitorování životního prostředí; chemické látky znečišťující vodu; látky znečišťující životní prostředí